AN INTERVENTION PROGRAME FOR THE PSYCHOSOCIAL NECESSITIES OF THE ELDERLY POPULATION OF TURKISH REPUBLIC OF NORTHERN CYPRUS - Esmaeilzadeh, Samineh; Oz, Fatma (International Journal of Psychosocial Rehabilitation, 2020)
As the necessities of the growing elderly population increase, the psychological requirements has increased the same amount. Nevertheless, the services for the elderly in our island can be insufficient on the cases of preserving and improving the psychosocial skills of the elderly. Nurses, who are one the pillar members of the medical teams, have a key role in the holistic care of the elderly. For this reason, there is a need for psychological and social care models on treatments of elderly citizens for the nurses besides the physical care. In this article, it has been aimed to propose a psychosocial intervention programme for the elderly citizens to minimize their problems specific to today, to make them more independent, and to help them overcome daily problems.